Konstrukční návrh manipulátoru motoru - Zvada, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Tato diplomová práce se zabývá rozborem manipulátorů. Na základě z nich získaných informací je navrhnuto konstrukční řešení manipulátoru motoru. Navržený manipulátor bude sloužit k závěrečné kontrole klikových skříní traktorů Zetor.

This master thesis deals with analysis of manipulators. After proposing several possibilities of some manipulator that are contemporary being used, there is suggested structural design for demanded motor manipulator. The proposed manipulator will be used for final control of crankcase for Zetor´s tractor.
Design of engine manipiulator
Keywords: Manipulátor; polohovadlo; motor; válečkový dopravník; Manipulator; positioner; engine; Roller conveyor